Penanggulangan Bencana Kekeringan di Kabupaten Bojonegoro dalam Perspekftif Good Governance - Bagas Aditya Dwilucky; Kalvin Edo Wahyudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Drought has become an annual disaster in Bojonegoro Regency. BPBD, which is a stakeholder responsible for disaster management efforts in the Bojonegoro Regency area, has collaborated with the private sector and civil society in overcoming this drought disaster. This study aims to describe the roles of three Good Governance actors, namely BPBD, the private sector, and also civil society in efforts to overcome drought in Bojonegoro Regency. This research uses descriptive qualitative research methods by obtaining data through observation, interviews, and documentation. The results of this study indicate that drought disaster management in Bojonegoro Regency has been running quite well. This is evidenced by the 3 Good Governance actors who have played an active role in drought disaster management efforts in Bojonegoro Regency in the pre-disaster phase and during a disaster. However, in the pre-disaster phase so far only BPBD has played an active role. The private sector and civil society have not played an active role. This research suggests that the BPBD of Bojonegoro Regency should strengthen cooperation with the private sector and civil society so that drought disaster management in Bojonegoro Regency can run optimally.